2009
DOI: 10.1158/1535-7163.mct-08-0759
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrofolate reductase amplification and sensitization to methotrexate of methotrexate-resistant colon cancer cells

Abstract: Gene amplification is one of the most frequent manifestations of genomic instability in human tumors and plays an important role in tumor progression and acquisition of drug resistance. To better understand the factors involved in acquired resistance to cytotoxic drugs via gene amplification, we have analyzed the structure and dynamics of dihydrofolate reductase (DHFR) gene amplification in HT29 cells treated with methotrexate (MTX). Analysis of the DHFR gene amplification process shows that the amplicon exhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 41 publications
1
35
0
1
Order By: Relevance
“…The hypodiploid group included the most DMspositive cases (27.2%). Morales et al reported that passive loss of the DHFR amplicon by the withdrawal of MTX results in MTX-sensitive cells exhibiting a substantial reduction of their capacity or even an incapacity to generate resistance when submitted to a second cycle of MTX treatment (Morales et al 2009). This phenomenon may be due to chromosome loss.…”
Section: Discussionmentioning
confidence: 99%
“…The hypodiploid group included the most DMspositive cases (27.2%). Morales et al reported that passive loss of the DHFR amplicon by the withdrawal of MTX results in MTX-sensitive cells exhibiting a substantial reduction of their capacity or even an incapacity to generate resistance when submitted to a second cycle of MTX treatment (Morales et al 2009). This phenomenon may be due to chromosome loss.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, loss of drug resistance is occasionally reported following drug withdrawal in vitro , 127,129133 although this mechanism is difficult to demonstrate in vivo . In xenograft models of RCC and hepatocellular carcinoma, tumours that had acquired resistance to sorafenib or sunitinib were shown to become resensitized to treatment after being transplanted into new hosts.…”
Section: Resistance Mechanismsmentioning
confidence: 99%
“…Methotrexate (MTX) is an essential drug in curative chemotherapy regimens and is used to treat patients with certain types of cancer including acute lymphoblastic leukemia, osteosarcoma, and choriocarcinoma. MTX works by disrupting DNA synthesis (Barnhart et al 2001); specifically, MTX inactivates the dihydrofolate reductase (DHFR) enzyme, which leads to the depletion of tetrahydrofolate cofactors that are required for DNA and RNA syntheses (Morales et al 2009). …”
Section: Introductionmentioning
confidence: 99%